2004
DOI: 10.1002/art.20654
|View full text |Cite
|
Sign up to set email alerts
|

Selective gray matter damage in neuropsychiatric lupus

Abstract: Objective. Damage of brain parenchyma in patients with primary diffuse neuropsychiatric systemic lupus erythematosus (NPSLE) has been indicated by magnetization transfer imaging (MTI). However, the location of MTI abnormalities is unknown. This study was undertaken to assess the distribution of MTI abnormalities over gray matter (GM) and white matter (WM) in SLE patients with a history of NP symptoms without explanatory magnetic resonance imaging (MRI) evidence of focal disease.Methods. MTI was performed in 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
2

Year Published

2005
2005
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 15 publications
4
46
1
2
Order By: Relevance
“…Low MTr indicates a reduced capacity of the protons in the brain tissue matrix to exchange magnetization with the surrounding water protons, which seems to be strongly associated with the degree of tissue (matrix) damage [17,30]. Several recent studies have demonstrated marked MTr reductions in lesional and normalappearing tissues of a number of neurological disorders [5,20,21,30,36]. As these reductions have been interpreted as the expression of subtle microscopic pathology possibly occurring in both myelin and axons [32], the low cortical-MTr found in our patients is likely to reflect a diffuse underlying structural pathology occurring in the cortex of DM1 brains.…”
Section: Discussionmentioning
confidence: 98%
“…Low MTr indicates a reduced capacity of the protons in the brain tissue matrix to exchange magnetization with the surrounding water protons, which seems to be strongly associated with the degree of tissue (matrix) damage [17,30]. Several recent studies have demonstrated marked MTr reductions in lesional and normalappearing tissues of a number of neurological disorders [5,20,21,30,36]. As these reductions have been interpreted as the expression of subtle microscopic pathology possibly occurring in both myelin and axons [32], the low cortical-MTr found in our patients is likely to reflect a diffuse underlying structural pathology occurring in the cortex of DM1 brains.…”
Section: Discussionmentioning
confidence: 98%
“…Autoantibodies in the CSF and immunocompetent cells in the choroid plexus of mice (Sakic et al, 2000b;Vogelweid et al, 1991) and the NP-SLE patient are further evidence that the blood-brain barrier in SLE becomes permeable to circulating factors (Abbott et al, 2003). Previous clinical studies had engendered the hypothesis that various brain-reactive antibodies (Denburg et al, 1993), cytokines, and toxic metabolites (Svenungsson et al, 2001;Trysberg et al, 2000) play principal roles in induction of SLEinduced brain damage in general, and gray matter in particular (Steens et al, 2004). With respect to the origin of autoantibodies, one of the important issues is whether they passively diffuse through the damaged blood-brain barrier or are synthesized intrathecally (i.e., within the brain).…”
Section: Discussionmentioning
confidence: 99%
“…For given subjects, the volume of each segmented compartment (in ml) is a convenient way of comparing segmentation methods. The segmentation method crucially affects the peak height estimate, which can be a sensitive measure of clinical status [10] (see Fig. 8).…”
Section: Imager Stability and Setupmentioning
confidence: 99%
“…The histogram is just a frequency distribution showing how many voxels there are at each value of a tissue parameter; it is usually normalised so that the total area under the curve is fixed (this reduces the effect of differing brain sizes). Extremely small changes can be detected, for example between different subgroups in multiple sclerosis (MS) [7,8] and systemic lupus erythematosus [9,10], and in serial studies of MS [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%